'Anchialine' Redefined as a Subterranean Estuary in a Crevicular or Cavernous Geological Setting. Issue 4 (1st July 2015) - Bishop, Renée E.; Humphreys, William F.; Cukrov, Neven; Žic, Vesna; Boxshall, Geoff A.; Cukrov, Marijana; Iliffe, Thomas M.; Kršinić, Frano; Moore, Willard S.; Pohlman, John W.; Sket, Boris
Abstract: An improved understanding of the anchialine ecosystem and geology warrants a redefinition of the term 'anchialine.' Originating from subareal biological observations, the term anchialine now encompasses chemical, physical, geological and biological elements within the subterranean realm. We propose a more accurate definition of the term anchialine as 'a tidally-influenced subterranean estuary located within crevicular and cavernous karst and volcanic terrains that extends inland to the limit of seawater penetration.' This subterranean estuary is characterized by sharp physical and chemical stratification and merges with a marine system at the coast and a groundwater system inland. The anchialine ecosystem supports a relatively diverse biotic assemblage of stygobiotic species of marine origin dominated by members of Crustacea, both numerically and by species richness.